Determinants of Regional Economics Growth - Sri Nawatmi; Agung Nusantara; Agus Budi Santosa (Media Ekonomi dan Manajemen, 2020)
This study aims to determine what factors influence regional economic growth. The analysis technique used is to combine time series data and cross-section (pooling data). Time-series data from 2015 - 2017 and cross section data consisting of 34 provinces in Indonesia. The results of the model test using the redundant fixed effect test and random effect-Hausman test show that the best model is the fixed effect model (FEM). Regression results show that only the HDI (Human Development Index) variable is not significant, the other variables (fiscal decentralization, capital, and labor) have a significant positive effect on regional economic growth.